2017
DOI: 10.1038/s41598-017-00065-3
|View full text |Cite
|
Sign up to set email alerts
|

A generalized model for time-resolved luminescence of localized carriers and applications: Dispersive thermodynamics of localized carriers

Abstract: For excited carriers or electron-hole coupling pairs (excitons) in disordered crystals, they may localize and broadly distribute within energy space first, and then experience radiative recombination and thermal transfer (i.e., non-radiative recombination via multi-phonon process) processes till they eventually return to their ground states. It has been known for a very long time that the time dynamics of these elementary excitations is energy dependent or dispersive. However, theoretical treatments to the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…In this study, we found that TNF-α levels in serum were increased during the fourth week, but no significant changes were seen during the 12th week (data not shown). These observations are consistent with the previous reports that acute PM exposure significantly increases inflammatory cytokine levels [ 66 ]. There were no significant changes in the levels of inflammatory cytokines after long-term PM 2.5 exposure [ 28 , 67 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we found that TNF-α levels in serum were increased during the fourth week, but no significant changes were seen during the 12th week (data not shown). These observations are consistent with the previous reports that acute PM exposure significantly increases inflammatory cytokine levels [ 66 ]. There were no significant changes in the levels of inflammatory cytokines after long-term PM 2.5 exposure [ 28 , 67 ].…”
Section: Discussionsupporting
confidence: 94%
“…Elevation of cAMP with forskolin in various cell types induces CREB phosphorylation at serine-133 and increases CREB-dependent transcription 30 , 44 46 . However, these studies use high concentrations of forskolin (typically 10–25 µM), which induce supra-physiological levels of cAMP in VSMC 4 . Consistent with these findings, we were also able to detect increased serine-133 phosphorylation in VSMC stimulated with 25 µM forskolin (Supplement Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This chaperone interacts with many proteins, including NDUS3 mentioned above [ 33 ]. In mitochondria, GRP75 helps to maintain mitochondrial shape and function [ 34 , 35 ]. The exposure to p , p‘- DDT strongly upregulated expression of GRP75 (see Tables 1 and 2 ), which may suggest that, after the exposure to DDT, mitochondria needed full support to maintain their functionality.…”
Section: Discussionmentioning
confidence: 99%